Conhecimento sobre asma em adolescentes - Andrade, Bárbara Bruna Fernandes de (2015)
Introduction: Asthma is a chronic disease whose effective management requires a close partnership between the asthmatic patient, your doctor and parents or caregivers. Adolescents with asthma have behaviors that complicate the diagnosis and adequate control of the disease, such as denial of symptoms, low perception of airflow obstruction, lack of adherence to treatment or inappropriate self-medication, far doctor-patient relationship. It is important that the patient acquires knowledge, confidence and ability to take care of their disease. Studies show that asthmatic and non-asthmatic adolescents and their teachers are unaware of information about asthma and its treatment. Evaluate the knowledge of asthma is the first step to organize an educational intervention in schools. Objective: To assess the knowledge of asthma in adolescents from public and private schools in the city of Aracaju. Methods: Cross sectional study of descriptive conducted in 64 schools in Aracaju with a sample of adolescents who participated previously in the ISAAC study in 2012. Three questionnaires were applied to characterize the population, knowledge of asthma and asthma control situation in the last month. Adolescents with asthma underwent spirometry. Quantitative variables were presented as mean and standard deviation or median and quartiles, and the categorical variables through simple and relative frequencies (%). To evaluate the student´s knowledge level, we used the one-dimensional model of Birnbaum 3 parameters based on Item Response Theory (IRT). To compare different epidemiological and demographic groups were used Student t test, ANOVA and Mann-Whitney. Score of knowledge and spirometric variables were associated using the linear correlation of Spearman. Results: We evaluated the knowledge of asthma in 355 adolescents aged 14 to 17 years, of which 87 were asthmatics. Sixty-four underwent spirometry. The score of knowledge was 46 (SD ± 12.79), considered insufficient. There was no difference in knowledge between asthmatics and non-asthmatics (45.08 vs 45.73; p = 0.65) or between educational institutions (45.73 vs 42.42 particular public; p = 0.08). Asthmatic adolescents of full age (r = 0.26; p = 0.035), higher education (39.78 vs 46.76 fundamental medium; p = 0.04) and FEV1 / FVC <80% (49.73 vs 40 45 FEV1 / FVC ≥ 80%; p = 0.004) showed higher scores of knowledge. Conclusion: Limited knowledge of adolescents about asthma indicates the need for education measures in order to demystify concepts of disease and bring benefits in the management of asthma patients.